SLR: Menurunkan Intensitas Remaja Perilaku Membolos Pada Siswa SMP Amanatullah Jajag Gambiran Banyuwangi - Sajidah, Ana; Masnida (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to explore the implementation of Self-Regulated Learning (SRL) in addressing truancy among students at SMP Amanatullah. The research employs a qualitative descriptive method with a case study approach. Data were collected through interviews, observations, and field notes, focusing on a 14-year-old student who frequently skipped school. The findings reveal that the primary causes of truancy are boredom with lessons, perceived difficulty of the material, and an overwhelming number of assignments. The implementation of SRL through individual counseling, goal setting, and metacognitive strategies effectively improved the student's learning motivation. Following the intervention, the frequency of truancy significantly decreased, and active engagement in the learning process increased. This study recommends the broader application of SRL in schools to enhance students' motivation and independent learning skills.